Inclusive innovation stems from environmental communication scholarship - Bernacchi, Leigh A. (Frontiers in Communication, 2024)
Environmental communication has led to expansive understanding of how to improve outcomes and processes to serve the underserved in natural resources and agricultural situations. As a practitioner, this article reflects on the pathway to build a profession outside of traditional academic careers to bring together diverse partners and disciplines.